Exploring the Pool of Pathogenic Variants of Amelogenesis Imperfecta: An Approach to the Understanding of Its Genetic Architecture - Urzúa, Blanca; Ortega-Pinto, Ana; Adorno-Farias, Daniela; Morales-Bozo, Irene; Rojas-Flores, Sandra; Briones-Marín, Diego; Lepiman-Torres, Constanza (Frontiers in Dental Medicine, 2021)
Objective: To identify which genes are associated with the clinical phenotype of AI and to elucidate which of these genes participate in the determination of isolated and syndromic forms. Methods: All data on mutations described in genes of AI were obtained from HGMD Professional 2020.2 (Trial version). The data in relation to the mutations, inheritance, phenotype, type of AI and country were supplemented with the literature. The identity codes and frequency values were consulted in dbSNP, ClinVar and OMIM databases. The percentage of specificity (PE) was determined for each gene. Results: HGMD describes 27 genes involved in Amelogenesis Imperfecta, which we propose to group into 5 categories: 1) genes whose mutations are associated only with isolated AI, 2) genes whose mutations only cause syndromic AI, 3) genes with causal mutations of AI isolated and mutations responsible for other pathologies, 4) genes with mutations responsible for syndromic AI and mutations that cause other pathologies and 5) genes that presents mutations that cause isolated AI, AI associated with syndromes and other pathologies. Using the PE calculation, the genes were ranked in 5 groups. The genes of category 1 are specific for isolated AI and the genes of categories 2 and 4 are nonspecific. Interestingly, we also observe that mutations in some genes have been associated with different types of cancer. Conclusion: ACP4, AMTN, MMP20, ODAPH, RELT, SLC24A4 and SP6 genes would participate in the determination of isolated AI and the CNNM4, DLX3 and FAM20A genes in syndromic forms of AI.